Right Unilateral Ultrabrief Pulse ECT in Geriatric Depression: Phase 1 of the PRIDE Study - Kellner, Charles H. (Am J Psychiatry, 2016)
OBJECTIVE: The Prolonging Remission in Depressed Elderly (PRIDE) study evaluated the efficacy of right unilateral ultrabrief pulse electroconvulsive therapy (ECT) combined with venlafaxine for the treatment of geriatric depression. METHOD: PRIDE was a two-phase multisite study. Phase 1 was an acute course of right unilateral ultrabrief pulse ECT, combined with open-label venlafaxine at seven academic medical centers. In phase 2 (reported separately), patients who had remitted were randomly assigned to receive pharmacotherapy (venlafaxine plus lithium) or pharmacotherapy plus continuation ECT. In phase 1, depressed patients received high-dose ECT (at six times the seizure threshold) three times per week. Venlafaxine was started during the first week of treatment and continued throughout the study. The primary outcome measure was remission, assessed with the 24-item Hamilton Depression Rating Scale (HAM-D), which was administered three times per week. Secondary outcome measures were post-ECT reorientation and safety. Paired t tests were used to estimate and evaluate the significance of change from baseline in HAM-D scores. RESULTS: Of 240 patients who entered phase 1 of the study, 172 completed it. Overall, 61.7% (148/240) of all patients met remission criteria, 10.0% (24/240) did not remit, and 28.3% (68/240) dropped out; 70% (169/240) met response criteria. Among those who remitted, the mean decrease in HAM-D score was 24.7 points (95% CI=23.4, 25.9), with a mean final score of 6.2 (SD=2.5) and an average change from baseline of 79%. The mean number of ECT treatments to remission was 7.3 (SD=3.1). CONCLUSIONS: Right unilateral ultrabrief pulse ECT, combined with venlafaxine, is a rapidly acting and highly effective treatment option for depressed geriatric patients, with excellent safety and tolerability. These data add to the evidence base supporting the efficacy of ECT to treat severe depression in elderly patients.